Prevalence of mutations in the cysteine desulfurase IscS (Pfnfs1) gene in recurrent Plasmodium falciparum infections following artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP) treatment in Matayos, Western Kenya - Beatrice Gachie; Kelvin Thiong’o; Brenda Muriithi; Jean Chepngetich; Noah Onchieku; Jeremiah Gathirwa; Peter Mwitari; Gabriel Magoma; Daniel Kiboi; Francis Kimani (Malaria Journal, 2023)
Abstract Background Malaria remains a public health concern globally. Resistance to anti-malarial drugs has consistently threatened the gains in controlling the malaria parasites. Currently, artemether-lumefantrine (AL) and dihydroartemisinin-piperaquine (DP) are the treatment regimens against Plasmodium falciparum infections in many African countries, including Kenya. Recurrent infections have been reported in patients treated with AL or DP, suggesting the possibility of reinfection or parasite recrudescence associated with the development of resistance against the two therapies. The Plasmodium falciparum cysteine desulfurase IscS (Pfnfs1) K65 selection marker has previously been associated with decreased lumefantrine susceptibility. This study evaluated the frequency of the Pfnfs1 K65 resistance marker and associated K65Q resistant allele in recurrent infections collected from P. falciparum-infected individuals living in Matayos, Busia County, in western Kenya. Methods Archived dried blood spots (DBS) of patients with recurrent malaria infection on clinical follow-up days after treatment with either AL or DP were used in the study. After extraction of genomic DNA, PCR amplification and sequencing analysis were employed to determine the frequencies of the Pfnfs1 K65 resistance marker and K65Q mutant allele in the recurrent infections. Plasmodium falciparum msp1 and P. falciparum msp2 genetic markers were used to distinguish recrudescent infections from new infections. Results The K65 wild-type allele was detected at a frequency of 41% while the K65Q mutant allele was detected at a frequency of 22% in the recurrent samples. 58% of the samples containing the K65 wild-type allele were AL treated samples and while 42% were DP treated samples. 79% of the samples with the K65Q mutation were AL treated samples and 21% were DP treated samples. The K65 wild-type allele was detected in three recrudescent infections (100%) identified from the AL treated samples. The K65 wild-type allele was detected in two recrudescent DP treated samples (67%) while the K65Q mutant allele was identified in one DP treated (33%) recrudescent sample. Conclusions The data demonstrate a higher frequency of the K65 resistance marker in patients with recurrent infection during the study period. The study underscores the need for consistent monitoring of molecular markers of resistance in regions of high malaria transmission.